Avaliação da eficiência de remoção de cor em função da distribuição de tamanho dos flocos e no fator de força - Borges, Marcelo Vandemberg Barbosa (2018)
After the formation of the flocs, they can deteriorate with the intensification of shear stresses, thus modifying all their morphological structure, reducing the efficiency of the process. The objective of this research was to evaluate the effect of ferric chloride concentration on the strength factor and size distribution of flocs formed from color water solution. Preliminarily, the coagulation / flocculation diagram of the study water was elaborated for one of the studied color conditions. After this step samples of different colors were treated, where it was evaluated the floc strength factor, the particle size distribution (DTP) and the color removal efficiency before and after the flakes rupture. Thus the objectives of the present work were to evaluate the evolution of the particle size distribution formed from different concentrations of coagulant and color conditions; to evaluate which particle distribution is more favorable to the color removal efficiency, as a function of the coagulant dosage and to evaluate the effect of the rupture in the distribution of the floc sizes. It was possible to observe, in general, the development of flakes between 0.05 and 2.75 mm, displacement of the particle size distribution (DTP) to larger size bands with increasing ferric chloride concentration and color and decrease in the process efficiency of 13%, on average, after the break.